Acoustic System of Determining the Instantaneous Volume of the Blood Part of the Ventricular Assist Device POLVAD-EXT - Grzegorz KONIECZNY; Tadeusz PUSTELNY; Zbigniew OPILSKI; Maciej GAWLIKOWSKI (Archives of Acoustics, 2014)
The paper presents the results of investigations concerning the noninvasive method of estimating the actual volume of the blood chamber of the POLVAD-EXT type ventricular assist device (VAD) during its operation. The proposed method is based on the principle of Helmholtz’s acoustic resonance. Both the theory, main stages of the development of the measurement method as well as the practical implementation of the proposed method in the physical model of the POLVAD-EXT device are dealt with. The paper contains the results of static measurements by means of the proposed method (conducted at the Department of Optoelectronics, Silesian University of Technology) as well as the dynamic measurements taken at the Foundation of Cardiac Surgery Development (Zabrze, Poland) with the professional model of the human cardiovascular system. The results of these measurements prove that the proposed method allows to estimate the actual blood chamber volume with uncertainties below 10%.